TRANSFORMASI KEPEMIMPINAN DALAM ORGANISASI PENDIDIKAN ISLAM: ANTARA NILAI SPIRITUAL DAN EVEKTIVITAS MANAJERIAL - Rohman, Fathur; Nasith, Ali; Ramadhan, Abdullah Rizki (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Leadership based on Islamic spiritual values ​​has been proven to make a real contribution to strengthening the religiosity of the school community. This is reflected in the application of the principles of integrity and trust, as well as transformational values ​​that encourage idealistic influence, inspiring motivation, more critical thinking, and attention to individual needs. Leadership transformation in Islamic educational institutions is a strategic issue amidst the currents of managerial modernization and the degradation of spiritual values. This study aims to identify the form and direction of Islamic educational leadership transformation that harmonizes spiritual values ​​with managerial effectiveness. The research approach uses a library method with qualitative descriptive analysis, sourced from scientific literature such as books, journal articles, and relevant research findings. The study's results indicate that effective leadership transformation does not solely emphasize technocratic dimensions, but must be grounded in the spirituality of monotheism that fosters integrity, sincerity, and moral responsibility. The synergy between spiritual values ​​and managerial skills produces a transformative, humanistic, and meaningful leadership model, thereby strengthening institutional performance and building an ethical and value-oriented organizational culture.